Writing in movement: movement-based performing arts for developing physical education teachers’ identity - Nicoletta Cappello; David Rodriguez; Esther Hernández; Dolors Cañabate (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This study highlights the relevance of surpassing Cartesian paradigms for a holistic development of Physical Education Teachers' identity through embodied pedagogies.